2018
DOI: 10.1002/adfm.201802852
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Fibrous Architectures for Drug Delivery, Tissue Engineering and Cancer Therapy

Abstract: The versatile electrospinning technique is recognized as an efficient strategy to deliver active pharmaceutical ingredients and has gained tremendous progress in drug delivery, tissue engineering, cancer therapy, and disease diagnosis. Numerous drug delivery systems fabricated through electrospinning regarding the carrier compositions, drug incorporation techniques, release kinetics, and the subsequent therapeutic efficacy are presented herein. Targeting for distinct applications, the composition of drug carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
146
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(147 citation statements)
references
References 264 publications
(305 reference statements)
0
146
0
1
Order By: Relevance
“…Degeneration of these cells results in changes in the extracellular matrix of the neural tissue that trigger a variety of clinical disorders. Since neurons cannot regenerate by themselves, restoration of their functions by means of biological and synthetic tools, processed in the form of fibrous scaffolds or biomolecule delivery systems, is a priority [139,140].…”
Section: Nervous Systemmentioning
confidence: 99%
“…Degeneration of these cells results in changes in the extracellular matrix of the neural tissue that trigger a variety of clinical disorders. Since neurons cannot regenerate by themselves, restoration of their functions by means of biological and synthetic tools, processed in the form of fibrous scaffolds or biomolecule delivery systems, is a priority [139,140].…”
Section: Nervous Systemmentioning
confidence: 99%
“…Prowadzone są również badania nad możliwością zastosowania nanowłókien w terapii nowotworowej [54][55][56][57][58]. Przykładowo Yang i współpr.…”
Section: Systemy Uwalniania Lekówunclassified
“…This altered release has been previously documented for changes in bre texture, the pH differences of core and shell bres and bre shell thickness however to the author's knowledge, changes to release rates due to charged nanoparticles within the mesh has not been previously observed. 38,39 However, it has been shown that in core-shell electrospinning, positively charged drugs are found to migrate to the surface of the bres compared to neutral drugs which remain in the core. 40 This is due to the charge generation of the surface of the polymer during electrospinning.…”
Section: Drug Release Studiesmentioning
confidence: 99%